Technology Acceptance Model (TAM): Measurement Of E- Learning Use by Accounting Students at Malang State University - Khafit, Abdul; Sulastri, Sulastri; Fauzan, Slamet (AIBPM Publisher, 2020)
Based on the Technology Acceptance Model (TAM) theory, the use of e-learning is influenced by perceived usefulness, perceived ease of use by adding other factors, namely self-confidence and subjective norms. This study aims to determine: (1) The effect of perceived usefulness on the use of e-learning; (2) The effect of perceived ease of use on the use of e-learning; (3) The effect of self-confidence on the use of e-learning; (4) The effect of subjective norms on the use of e-learning. The Explanation Approach is used to explore the data in this study. The population in this study was the 2016 Accounting Education Bachelor Program students, amounting to 116 students. The number of samples in this study were 116 students. Collecting data in this study using a questionnaire with a Likert scale as a measure of research variables. Analysis of the data used is multiple linear regression. The results of this study indicate that the perceived usefulness, perceived ease of use, self-confidence, and subjective norms have a significant effect on the use of e-learning.